Chronic inhibition, self-control and eating behavior: Test of a 'resource depletion' model - Hagger, Martin; Panetta, G.; Leung, C.; Wong, Ging; Wang, J.; Chan, Derwin; Keatley, D.; Chatzisarantis, Nikos (Public Library of Science, 2013)
The current research tested the hypothesis that individuals engaged in long-term efforts to limit food intake (e.g., individuals with high eating restraint) would have reduced capacity to regulate eating when self-control resources are limited. In the current research, body mass index (BMI) was used as a proxy for eating restraint based on the assumption that individuals with high BMI would have elevated levels of chronic eating restraint. A preliminary study (Study 1) aimed to provide evidence for the assumed relationship between eating restraint and BMI. Participants (N = 72) categorized into high or normal-range BMI groups completed the eating restraint scale. Consistent with the hypothesis, results revealed significantly higher scores on the weight fluctuation and concern for dieting subscales of the restraint scale among participants in the high BMI group compared to the normal-range BMI group. The main study (Study 2) aimed to test the hypothesized interactive effect of BMI and diminished self-control resources on eating behavior. Participants (N = 83) classified as having high or normal-range BMI were randomly allocated to receive a challenging counting task that depleted self-control resources (ego-depletion condition) or a non-depleting control task (no depletion condition). Participants then engaged in a second task in which required tasting and rating tempting cookies and candies. Amount of food consumed during the taste-and-rate task constituted the behavioral dependent measure. Regression analyses revealed a significant interaction effect of these variables on amount of food eaten in the taste-and-rate task. Individuals with high BMI had reduced capacity to regulate eating under conditions of self-control resource depletion as predicted. The interactive effects of BMI and self-control resource depletion on eating behavior were independent of trait self-control. Results extend knowledge of the role of self-control in regulating eating behavior and provide support for a limited-resource model of selfcontrol.